Correlate of Workforce Diversity and Organisational Performance of Multinational Food Producing Industry in Nigeria - Kowo Solomon Akpoviroro; Kadiri Bolarinwa Ismaila; Zekeri Abu (Business Ethics and Leadership)
The paper summarizes the arguments and counterarguments within the scientific discussion on the issue cultural and age diversity of workforce and the level of workers’ productivity in the multinational companies. Three hundred and seventy-five employees from five multinational food companies in Southwest Nigeria form the object of the research. Methodological research tools contain questionnaires; the regression analysis methods was used when testing hypotheses on the existence of a correlation between cultural diversity and team performance; cross-tabulation analysis method; inter-position correlation test, and ANOVA method for generalizing and interpreting the results. The results of the study regarding the relationship between a company’s cultural diversity and its market share showed that cultural diversity does not affect the performance of the organization’s employees, while work experience has a non-linear impact on the company’s productivity. The results of findings conclude that there is a link between workforce diversity and the organizational effectiveness of the company, as well as the positive relationship between the cultural diversity of employees and their work experience. The findings of the study are agreed with the work of other scientists on the subject and complement their results. According to the results of the analysis, it was concluded that it is necessary to increase the level of awareness of the staff about the cultural diversity that exists in the organization. The reason is that it is necessary to increase the employees’ morale and their work efficiency, which will increase the level of customer satisfaction with the work of the company. The study recommends that; multinational food producing industries should not only ensure employee diversity in their businesses but they should also make sure that diversity is used to improve organizational performance. Future research in this area should focus on consideration of all stakeholders’ opinions in the formulation of multinational company’s personnel policies.